Giving way : thoughts on unappreciated dispositions - Connor, Steven, 1955- (Stanford University Press, 2019)
"In a world that promotes assertion, agency, and empowerment, this book challenges us to revalue a range of actions and attitudes that have come to be disregarded or dismissed as merely passive. Mercy, resignation, politeness, restraint, gratitude, abstinence, losing well, apologizing, taking care: today, such behaviors are associated with negativity or lack. But the capacity to give way is better understood as positive action, at once intricate and demanding. Moving from intra-human common courtesies, to human-animal relations, to the global civility of human-inhuman ecological awareness, the book's argument unfolds on progressively larger scales. In reminding us of the existential threat our drives pose to our own survival, Steven Connor does not merely champion a family of behaviors; he shows that we are more adept practitioners of them than we realize. At a time when it is on the wane, Giving Way offers a powerful defense of civility, the versatile human capacity to deflect aggression into sociability and to exercise power over power itself." --